Gender Differences in Risks of Coronary Heart Disease and Stroke in Patients with Type 2 Diabetes Mellitus and Their Association with Metabolic Syndrome in China. (30th November 2016) - Yao, Mei-Fang; He, Jie; Sun, Xue; Ji, Xiao-Li; Ding, Yue; Zhao, Yi-Ming; Lou, Han-Yu; Song, Xiao-Xiao; Shan, Li-Zhen; Kang, Ying-Xiu; Zhang, Song-Zhao; Shan, Peng-Fei
Abstract : Coronary heart disease (CHD) and stroke are common complications of type 2 diabetes mellitus (T2DM). We aimed to explore the differences in the risks of CHD and stroke between Chinese women and men with T2DM and their association with metabolic syndrome (MS). This study included 1514 patients with T2DM. The Asian Guidelines of ATPIII (2005) were used for MS diagnosis, and the UKPDS risk engine was used to evaluate the 10-year CHD and stroke risks. Women had lower CHD risk (15.3% versus 26.3%), fatal CHD risk (11.8% versus 19.0%), stroke risk (8.4% versus 10.3%), and fatal stroke risk (1.4% versus 1.6%) compared with men with T2DM (p < 0.05 –0.001). The CHD risk (28.4% versus 22.6%, p < 0.001 ) was significantly higher in men with MS than in those without MS. The CHD (16.2% versus 11.0%, p < 0.001 ) and stroke risks (8.9% versus 5.8%, p < 0.001 ) were higher in women with MS than in those without MS. In conclusion, our findings indicated that Chinese women with T2DM are less susceptible to CHD and stroke than men. Further, MS increases the risk of both these events, highlighting the need for comprehensive metabolic control in T2DM.